A history of Rome down to the reign of Constantine - Cary, M. 1881-1958 (Macmillan; St. Martins Press, 1954)
Classical work on the history of the Roman Empire - For senior history students - Many illustrations of Roman antiquities - Map of ancient Rome - Map of the Roman Empire under Augustus, Trajan and Hadrian - Lazio (Latium) - Rome.